2019
DOI: 10.1021/acs.jpclett.9b01939
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Energy Transfer in a Binary Colloidal Quantum Well Complex

Abstract: Forster resonance energy transfer (FRET) is a fundamental process that is key to optical biosensing, photosynthetic light harvesting, and downconverted light emission. However, in total, conventional FRET in a donor− acceptor pair is essentially unidirectional, which impedes practical application of FRET-based technologies. Here, we propose a mutual FRET scheme that is uniquely bidirectional in a binary colloidal quantum well (CQW) complex enabled by utilizing the d orbital electrons in a dopant−host CQW syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Copper ions doped into CdSe CQWs can be realized by using both nucleation doping and partial cation exchange. [22,[27][28][29][30] However, the nucleation doping method generally results in rectangular-shaped CQWs which are difficult for long-range stacking. For this work, we prefer doped and undoped CQWs with similar dimensions to construct the binary superlattice, therefore, we follow our earlier report on partial cation exchange recipes, where we add a controllable amount of copper acetate precursor into a solution of square-shaped undoped four ML core CQWs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Copper ions doped into CdSe CQWs can be realized by using both nucleation doping and partial cation exchange. [22,[27][28][29][30] However, the nucleation doping method generally results in rectangular-shaped CQWs which are difficult for long-range stacking. For this work, we prefer doped and undoped CQWs with similar dimensions to construct the binary superlattice, therefore, we follow our earlier report on partial cation exchange recipes, where we add a controllable amount of copper acetate precursor into a solution of square-shaped undoped four ML core CQWs.…”
Section: Resultsmentioning
confidence: 99%
“…modify the preference of exciton recombination channel via band-edge emission (BE) or copper emission (CE) due to an ultralong exciton hopping range (>100 nm) [17,20] and an ultrafast exciton hopping rate (≈4 ps). [11,17,22] By enlarging the vertical dimension of the binary superlattice, more photoexcited excitons are harvested by Cu dopants and as a result, the greenish and anisotropy photoluminescence (the intrinsic emission properties of BE) [12,13] is gradually changed into the reddish and isotropy photoluminescence (the intrinsic emission properties of CE). [22,23] In addition, we have modeled the excitonic dynamics (including exciton transfer, exciton trapping, and exciton recombination) in the binary superlattice, which can well-reproduce the controllability observed in the experiments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the perspective of fundamental understanding, the role of dopants in the bandgap modulation and steadystate/transient photoluminescence (PL) has been investigated into great depth. [5,[7][8][9][10][11] From the perspective of application, benefiting from the nearly zero self-absorption in the dopant related emission, Sharma et al demonstrated near-unity photoluminescence quantum yields in the luminescent solar concentrators using copper-doped colloidal quantum wells (CQWs). [4] To date, majority of the works on TMDCNMs are conducted with low pump fluence/intensity (i.e., stay in the sub-single/single exciton regime) and the potential of TMD-CNMs as optical gain materials has not aroused much attention.…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of fundamental understanding, the role of dopants in the bandgap modulation and steady‐state/transient photoluminescence (PL) has been investigated into great depth. [ 5,7–11 ] From the perspective of application, benefiting from the nearly zero self‐absorption in the dopant related emission, Sharma et al. demonstrated near‐unity photoluminescence quantum yields in the luminescent solar concentrators using copper‐doped colloidal quantum wells (CQWs).…”
Section: Introductionmentioning
confidence: 99%